Effect of thyme-ivy syrup on antiviral immune response in patients with mild COVID-19: a prospective, open-label, randomized pilot study - Dauth, Stephanie; Schäfer, Stephan M. G.; Klippstein, Maximilian; Foldenauer, Ann C.; Jonetzko, Christin; Roßmanith, Tanja; Schiffmann, Susanne; Vehreschild, Maria J. G. T.; Geisslinger, Gerd; Behrens, Frank; Koehm, Michaela (Frontiers in Medicine, 2025)
BackgroundThyme-ivy syrup has anti-inflammatory activities and exerts beneficial effects on symptom relief and recovery time in patients with acute bronchitis. The objective of this exploratory study was to evaluate the effect of thyme-ivy syrup on immune response mediators in patients with mild COVID-19.MethodsThis prospective, open-label, randomized, controlled, single-center pilot study (BroVID study; EudraCT 2021–003237-11) was conducted in adult outpatients with mild COVID-19, cough, and ≥1 additional symptom. Patients were randomly assigned to the thyme-ivy syrup group, which received three 5.4 mL doses of oral thyme-ivy syrup per day for 14 days, or a control group (no medication) in a 2:1 ratio. The primary objective was to demonstrate a clinically relevant treatment difference between the two groups in change from baseline to day 7 in blood parameters involved in the immune response, including interleukin (IL)-6, IL-10, tumor necrosis factor, and specific blood cell types. Secondary objectives included assessments of other blood parameters and time points, symptoms, and quality of life. Adverse events were reported at each study visit.ResultsTwenty-one patients were enrolled in and completed the study (13 in the thyme-ivy syrup group, 8 in the control group). On day 7, numerically greater decreases in the thyme-ivy syrup group were observed for some mediators, including IL-10 (−17.7 vs. − 6.0 pg/mL; effect size 0.53) and IL-6 levels (−4.9 vs. − 0.9 pg/mL; effect size 0.87). Significant between-group differences were observed for changes in some parameters at day 4 (e.g., IL-10) and day 14. Baseline characteristics differed between the two groups, including a higher viral load, shorter duration of symptoms prior to study start, elevated levels of inflammatory markers, and more comorbidities in the thyme-ivy syrup group compared with control. Thyme-ivy syrup was well tolerated.ConclusionThe exploratory BroVID study identified treatment differences in immune response mediators with moderate to large effect sizes for thyme-ivy syrup vs. control in patients with mild COVID-19; these differences require validation in a larger confirmatory study. The findings may be subject to bias due to imbalanced baseline characteristics, the inter- and intra-individual heterogeneity of inflammatory markers, and the small sample size.